Assessing Turkey's secondary schools performance by different region in 2006 - Demir, Ibrahim; Depren, Ozer (ELSEVIER SCIENCE BV, 2010)
The low performance of Turkey in the Programme for International Student Assessment (PISA 2003 and 2006) was a great disappointment for that country. To investigate the likely causes for low performance in mathematics, reading and science, this study utilizes the methodology of data envelopment analysis (DEA) to assess the efficiency of secondary schools in Turkey using data from Programme for International Student Assessment (PISA) in 2006. The sample was prepared from schools which participated in Programme for International Student Assessment (PISA) in Turkey. Efficient and inefficient schools in Turkey were determined by analyzing the sample data by grouping schools by regions. As a result of the study, we found that 17 of the 33 schools in different regions were efficient. The most efficient school types are Science High Schools and Anatolian Vocational High Schools. Furthermore, we examined schools which were located in different region in Turkey and found that 2 of the 2 Science High Schools (%100), 4 of the 5 Anatolian Vocational High Schools (%80), 4 of the 6 Secondary and Vocational High Schools (%66.7), 3 of the 6 Anatolian Schools (%50.0), 3 of the 7 Vocational High Schools (%42.9) and 1 of the 7 General High Schools were efficient. As a result of this study it is found that even same type of schools which were located in different region have a different characteristic on the achievement. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Data envelopment analysis; secondary school achievement; PISA; Education & Educational Research